PENGARUH IRRADIASI SINAR GAMMA Co-60 TERHADAP VIABILITAS KOKON DAN PERKEMBANGAN CACING TANAH (Lumbricus rubellus Hoff.) - , NADEA FELISAN A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Earthworm is important organism in life, such as Lumbricus rubellus Hoff has an important organism on organic decomposer of soil substances, as an alternative food for animals and fish, and also as a medicine. Earthworm Lumbricus rubellus Hoff. has fast reproductivity and is easy to cultivated. The manipulation on the reproductive system of earthworms can be treated in various of ways. One of these, is the use of ionizing radiation technique by gamma Co-60 irradiator. This research was conducted to study the effect of Gamma Co-60 irradiation on cocoon viability and development of Lumbricus rubellus Hoff. Futhermore this research is to determinate the optimum dose of irradiation which has an significant effect on cocoon viability and development of earthworms (Lumbricus rubellus Hoff.). Cocoons were irradiated by gamma Co-60 irradiator in 6 various doses (0 Gy as control